Economic growth and human development - Ranis, Gustav (2000)
Identifies the major links between economic growth and human development. Presents some empirical crosscouontry evidence on these links. Develops a typology of country cases, some representing the mutual enhancement of human development and some demonstrating asymmetric performance. Investigates the movement of countries from one category to another and reflects on the implications for policy.